Optimasi Variasi Konsentrasi, Waktu Sentrifugasi Polyethylene Glycol (PEG), dan Modified Egg Yolk Lipemic Serum pada Enzim Serum Glutamic Pyruvic Transaminase (SGPT) - Susilawati, Anissa; Riyani, Ani (Sekolah Tinggi Ilmu Kesehatan Rajawali, 2023)
Examination of Serum Glutamic Pyruvic Transaminase (SGPT) enzymes can be disrupted due to the presence of fatty serum. The addition of Polyethylene Glycol (PEG) to fatty serum will lower the surface tension of the serum so that the fat will precipitate and eliminate error readings on the photometer. This study aims to determine the concentration and centrifugation time of the addition of Polyethylene Glycol (PEG) under optimal conditions. Serum modification was made to resemble fatty serum using egg yolks with three variations of triglyceride levels in ±500 mg/dL, ±600 mg/dL, ±700 mg/dL. Fatty serum is made using three concentrations of Polyethylene Glycol (PEG), namely 0.05%, 0.10%, 0.15%. Then incubated for 30 minutes at 40C and precipitation was carried out using centrifugation at 3000 rpm with three variations of centrifugation time, namely at 5, 10 and 15 minutes. Then the resulting supernatant was separated and measured to determine the Serum Glutamic Pyruvic Transaminase (SGPT) enzyme using a photometer. Then the data were analyzed using a two way ANOVA test followed by a Post Hoc test with a 95% confidence level. The conclusion of this study is that at 500 mg/dL fatty serum, the optimal concentration was obtained, namely 0.10% with a 10-minute centrifugation time, at 600 mg/dL fatty serum, the optimal concentration was obtained, namely 0.10% with a 10-minute centrifugation time, on fatty serum 700 mg/dL obtained the optimal PEG concentration and centrifugation time of 0.15% with a centrifugation time of 15 minutes.